2023
DOI: 10.1093/ornithology/ukad009
|View full text |Cite
|
Sign up to set email alerts
|

Beaver activity and red squirrel presence predict bird assemblages in boreal Canada

Abstract: Wetlands and predation in boreal ecosystems play essential roles throughout the breeding season for bird assemblages. We found a positive association of beaver activity and a negative influence of American red squirrels (Tamiasciurus hudsonicus) on bird assemblages. We used a multispecies hierarchical model to investigate whether bird communities differ between two major wetland habitats in boreal Canada: beaver ponds and peatland ponds. In addition to including variables such as forest cover and latitude, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 121 publications
1
2
1
Order By: Relevance
“…A similar pattern was observed for marsh birds in buffers within 0.5 km from the wetland edge (Smith and Chow-Fraser 2010). Nonetheless, the lack of general effects of forest cover found here disagrees with patterns identi ed for 10 of 35 species using acoustic recorders in the same ponds (Feldman et al 2023a). These discrepancies could be due to differences in sampling methods: camera traps detect individuals within a smaller area than acoustic recorders (Shon eld and Bayne 2017; Darras et al 2018).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…A similar pattern was observed for marsh birds in buffers within 0.5 km from the wetland edge (Smith and Chow-Fraser 2010). Nonetheless, the lack of general effects of forest cover found here disagrees with patterns identi ed for 10 of 35 species using acoustic recorders in the same ponds (Feldman et al 2023a). These discrepancies could be due to differences in sampling methods: camera traps detect individuals within a smaller area than acoustic recorders (Shon eld and Bayne 2017; Darras et al 2018).…”
Section: Discussioncontrasting
confidence: 89%
“…On the other hand, the detection probability of beaver and 21 bird species decreased substantially with the number of days since snowmelt, meaning that detectability is higher at the beginning of the season. The same pattern was detected in our acoustic approach (Feldman et al 2023a), where 18 out of 35 bird species showed the same response, mainly for aquatic species. The Wood Duck was the only species detected later in the season, which would be consistent with patterns of several waterfowl species where molting occurs far from breeding grounds (Hepp and Bellrose 2020), although the effect of days since snowmelt was marginal.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations